Patterns of Discourse in Two Kinds of Literature Discussion - Chinn, Clark A.; Anderson, Richard C.; Waggoner, Martha A. (Reading research quarterly, 2001)
This study examines the effects of two different instructional frames for discussion--traditional Recitations and an alternative to Recitations called Collaborative Reasoning--on patterns of discourse in fourth-grade literature discussions. These two instructional frames differ on four key parameters that define an instructional frame: (a) the stance to be taken. (b) who holds interpretive authority, (c) who controls turntaking, and (d) who controls the topic of the discourse. Two research questions were addressed. The first question was whether it is possible for fourth-grade teachers and their students to implement Collaborative Reasoning, an instructional frame that transfers much of the control over discourse to students, during their reading lessons. Quantitative analyses were conducted of features of discourse including turntaking, teacher questions, and cognitive processes manifested in students' talk. The results showed that the teachers and students were generally successful at implementing the new instructional frame. It proved more difficult to shift control over topic and turntaking to students than to shift interpretive authority to students. The second question addressed the effects of the new instructional frame on patterns of discourse. In comparison to Recitations, Collaborative Reasoning discussions produced greater engagement and more extensive use of several higher level cognitive processes. The results provide support for the use of Collaborative Reasoning in fourth-grade reading lessons. /// [Spanish] Este estudio examina los efectos de dos tipos diferentes de esquemas didácticos de discusión--el Recitado tradicional y una alternativa al Recitado llamada Razonamiento en Colaboración, sobre los patrones discursivos en las discusiones sobre literatura en cuarto grado. Estos dos esquemas didácticos difieren en cuatro parámetros clave que definen un esquema didáctico: (a) la postura que se toma, (b) quién tiene autoridad interpretativa, (c) quién controla los turnos en la interacción y (d) quién controla el tópico del discurso. Se formularon dos preguntas para la investigación. La primera pregunta fue si era posible para los docentes y estudiantes de cuarto grado implementar el Razonamiento en Colaboración, un esquema didáctico que transfiere gran parte del control sobre el discurso a los estudiantes durante las clases de lectura. Se realizaron análisis cuantitativos de aspectos del discurso que incluyeron toma de turnos, preguntas del docente y procesos cognitivos manifestados en el discurso de los estudiantes. Los resultados mostraron que los docentes y estudiantes generalmente tuvieron éxito en la implementación del nuevo esquema didáctico. Resultó más difícil otorgar el control sobre el tópico y los turnos a los estudiantes que la autoridad interpretativa. La segunda pregunta se refirió a los efectos del nuevo esquema didáctico sobre los patrones discursivos. En comparación con los Recitados, las discusiones en el esquema Razonamiento en Colaboración produjeron mayor compromiso y un uso más extenso de procesos cognitivos superiores. Los resultados proporcionan apoyo al uso de Razonamiento en Colaboración en las clases de lectura de cuarto grado. /// [German] Diese Studie untersucht die Auswirkungen von zwei unterschiedlichen Unterrichtsrahmen zwecks Diskussion--traditionelle Rezitationen und eine Alternative zu Rezitationen, genannt Kollaborative Beurteilungsauseinandersetzung--über Formen der Meinungsabweichung in Schreib- und Lesediskussionen der vierten Klasse. Diese zwei Unterrichtsrahmen unterscheiden sich bei den vier Schlüsselparametern, welche einen Unterrichtsrahmen definieren: (a) die einzuschlagende Haltung, (b) wer verfügt über interpretative Autorität, (c) wer kontrolliert das Ablösen, und (d) wer kontrolliert das Thema der Meinungsabweichung. Zwei Forschungsfragen wurden angesprochen. Die erste Frage bestand darin, ob es den Lehrern und Schülern der vierten Klasse möglich ist, die Kollaborative Beurteilungsauseinandersetzung zu implementieren, also einen Unterrichtsrahmen einzuführen, der eine wesentliche Kontrolle über Meinungsunterschiede während ihres Leseunterrichts an die Schüler überträgt. Es wurden quantitative Analysen der Hauptmerkmale der Meinungsabweichungen durchgeführt, einschließlich des Ablösens, der Fragen der Lehrer, sowie der in den Schülererörterungen manifestierten kognitiven Erkennungsprozesse. Die Ergebnisse zeigten, daß die Lehrer und Schüler im allgemeinen erfolgreich bei Einführung des neuen Unterrichtsrahmens waren. Es erwies sich als schwieriger, die Kontrolle über Thema und Ablösung auf die Schüler zu übertragen, als das Verlagern von interpretativer Autorität auf die Schüler. Die zweite Frage wendete sich an die Auswirkungen des neuen Unterrichtsrahmens auf Musterformen der Meinungsabweichungen. Im Vergleich zu Rezitationen lieferten die kollaborativen Beurteilungsdiskussionen größeres Engagement und einen ausführlicheren Gebrauch von mehreren hochgradig kognitiven Prozessen. Die Ergebnisse rechtfertigen die Verwendung der Kollaborativen Beurteilungsauseindersetzung in Lesestunden der vierten Klasse. /// [French] Cette étude examine les effets de deux formes didactiques différentes de discussion, la récitation traditionnelle et une forme alternative nommée « raisonnement en collaboration », sur la structure du discours dans des discussions littéraires en 4° année. Ces deux formes didactiques diffèrent suivant quatre paramètres clé qui définissent une forme didactique: a) le point de vue adopté, b) qui détient l'autorité interprétative, c) qui contrôle la prise de parole, d) qui contrôle le thème du discours. On s'est posé deux questions de recherche. La première question était de savoir s'il est possible à des enseignants de 4° année et à leurs élèves de mettre en place un raisonnement en collaboration, c'est-à-dire une forme didactique qui transfère aux élèves une bonne part du contrôle sur le discours pendant les heures de lecture. On a effectué des analyses quantitatives des caractéristiques du discours, comprenant le tour de parole, les questions du maître, et des processus cognitifs apparus dans la parole des élèves. Les résultats ont montré que les enseignants et les élèves ont généralement réussi à mettre en place la nouvelle structure didactique. Il s'est avéré plus difficile de confier le contrôle sur le thème et la prise de parole aux élèves que de leur confier l'autorité interprétative. La seconde question concernait les effets de la nouvelle structure interprétative sur les patrons de discours. Comparées aux récitations, les discussions lors du raisonnement en collaboration ont produit une plus grande implication et une plus grande utilisation de plusieurs processus cognitifs de haut niveau. Les résultats plaident en faveur d'une utilisation du raisonnement en collaboration pendant les cours de lecture de 4° année. /// [Cyrillic] В данном исследовании рассматриваются результаты двух различных подходов к организации беседы в процессе обучения на уроках литературы в четвертом классе: традиционный - основанный на пересказе, и так называемое коллективное рассуждение. Эти два подхода различаются по четырем ключевым параметрам: (а) стиль общения, (б) кто доминирует в интерпретации текста, (в) кто контролирует очередность высказываний, (г) кто контролирует соответствие обсуждения теме. Исследовалось два вопроса. Первый: по силам ли учителям организовать с учащимся четвертого класса коллективное рассуждение, т.е. использовать обучающую модель, при которой контроль над беседой на уроках чтения в основном осуществляется учащимися. Был проведен количественный анализ таких параметров общения, как очередность высказывания, вопросы учителя и виды познавательной деятельности, продемонстрированные учащимися в ходе беседы. Полученные результаты показывают, что учителя и учащиеся в основном успешно справляются с работой по новой модели обучения. Оказалось, что передать детям контроль над соответствием обсуждения заданной теме и очередностью высказываний куда труднее, чем над интерпретацией текста. Второй вопрос заключался в том, как новая модель обучения влияет на тип дискурса. По сравнению с урокомпересказом в коллективном рассуждении приняли участие значительно больше учащихся, продемонстрировав при этом несколько видов познавательной деятельности высокого порядка. Полученные результаты подтверждают целесообразность использования коллективного рассуждения на уроках чтения в четвертом классе.